Pendampingan Partisipatif dalam Perumusan Kebijakan Minapolitan Berbasis Hilirisasi Produk Perikanan untuk Perencanaan Wilayah Berkelanjutan di Banggai Kepulauan - Reinal Putalan; Muh. Nur Sangadji; Rostiaty Rahmatu; Irwan Lakani; Selvy Mozin; Maulidin Kurniawan; Septian Palma Ariany (Program Vokasi Universitas Negeri Gorontalo, 2026)
Banggai Kepulauan Regency faces challenges in declining capture fishery production and economic leakage due to illegal mid-sea transactions. This community service activity aimed to facilitate the participatory formulation of fishery downstreaming policies to support the Minapolitan vision in regional planning. The method employed was descriptive qualitative with technocratic mentoring through a series of Focus Group Discussions (FGD) and Public Consultations. Results indicated that fishery issues rank as the second strategic priority in the region's sustainable development agenda. The process successfully formulated recommendations for processing infrastructure integration, including the development of Small and Medium Industries (IKM) in Sambiut and Kalumbatan Villages, and optimized Fish Auction Sites (TPI) to terminate illegal trade chains. It is concluded that inclusive policy facilitation can synchronize fishing community economic needs with coastal ecosystem protection mandates. Downstreaming serves as a key solution to increase local value-added and accelerate sustainable development in Banggai Kepulauan Regency.